Phenotypic variations of TRAIL sensitivity in cloned populations of prostate cancer cells - Cross, N; Waterman, E; Jokonya, N; Fowles, A; Buckle, C; Phillips, J; Holen, I; Hamdy, F; Eaton, C (2008)
Factors that regulate the induction of apoptosis of tumour cells are potential candidates for therapeutic intervention for the majority of cancers. Studying modifiers of apoptotic responses, such as members of the tumour necrosis factor receptor superfamily, may give clues as to how induction of apoptosis in tumours could be maximized to enhance the benefit of treatment regimes. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising anti-tumour molecule since its activity is specific for tumour cell populations. TRAIL binds to death receptors, inducing apoptosis in susceptible cells. The mechanisms which determine whether tumour cells are susceptible to TRAIL are unclear, and several mechanisms have been proposed, including expression of osteoprotegerin (OPG), decoy receptors, and factors that affect intracellular signalling of pro-apoptotic molecules, such as c-FLIP. Here we show that experiments to modulate the activity of one of these factors, OPG, by over-expression and also by stable knockdown of OPG expression, alters the TRAIL sensitivity of PC3 prostate cancer cells. However we show that some observed effects, which appear to support the hypothesis that OPG prevents TRAIL-induced apoptosis of tumour cells, may be due to variation of the TRAIL response of sub-clones of tumour cells, even within a cloned population. These results highlight potential limitations of experiments designed to test contribution of factors affecting intrinsic apoptosis susceptibility using cloned tumour cell populations. © 2008 Wiley-Liss, Inc.